The little grey girl - Kiernan, Celine (Kiernan, Celine. Wild magic trilogy, 2019)
The old queen may not have been killed, but for now she has been defeated, leaving Mup and her family free to move into the queen's old castle. Mup is just settling into her new room and home when an enchanted snowfall cuts the castle off from the rest of the kingdom, trapping Mup, her family, the queen's former servants, a reformed raggedy witch, and a ghostly physician inside. Just now, of course, Mup finds out the castle is haunted.